Bioenergetic Phenotyping of DEN-Induced Hepatocellular Carcinoma Reveals a Link Between Adenylate Kinase Isoform Expression and Reduced Complex I-Supported Respiration - McLaughlin, Kelsey L.; Nelson, Margaret A.M.; Coalson, Hannah S.; Hagen, James T.; Montgomery, McLane M.; Wooten, Ashley R.; Zeczycki, Tonya N.; Vohra, Nasreen A.; Fisher-Wellman, Kelsey H. (Frontiers in Oncology, 2022)
Hepatocellular carcinoma (HCC) is the most common form of liver cancer worldwide. Increasing evidence suggests that mitochondria play a central role in malignant metabolic reprogramming in HCC, which may promote disease progression. To comprehensively evaluate the mitochondrial phenotype present in HCC, we applied a recently developed diagnostic workflow that combines high-resolution respirometry, fluorometry, and mitochondrial-targeted nLC-MS/MS proteomics to cell culture (AML12 and Hepa 1-6 cells) and diethylnitrosamine (DEN)-induced mouse models of HCC. Across both model systems, CI-linked respiration was significantly decreased in HCC compared to nontumor, though this did not alter ATP production rates. Interestingly, CI-linked respiration was found to be restored in DEN-induced tumor mitochondria through acute in vitro treatment with P1,P5-di(adenosine-5′) pentaphosphate (Ap5A), a broad inhibitor of adenylate kinases. Mass spectrometry-based proteomics revealed that DEN-induced tumor mitochondria had increased expression of adenylate kinase isoform 4 (AK4), which may account for this response to Ap5A. Tumor mitochondria also displayed a reduced ability to retain calcium and generate membrane potential across a physiological span of ATP demand states compared to DEN-treated nontumor or saline-treated liver mitochondria. We validated these findings in flash-frozen human primary HCC samples, which similarly displayed a decrease in mitochondrial respiratory capacity that disproportionately affected CI. Our findings support the utility of mitochondrial phenotyping in identifying novel regulatory mechanisms governing cancer bioenergetics.